Analysis of the association between problem behaviors and Sasang typology in high school students - Mi Hwa Choi; Han Chae; Soo Jin Lee (Integrative Medicine Research)
Background: Some studies have shown that Sasang typology is related to specific problem behaviors, but research on the associations between Sasang types and problem behaviors in children is scarce. The purpose of this study was to examine the associations between Sasang types and problem behaviors in Korean high school students. Methods: A total of 686 Korean high school students (371 boys and 315 girls) completed the Korean version of Youth Self-Report (YSR) for describing the problem behaviors in adolescents and the Sasang Personality Questionnaire (SPQ) for measuring the temperament characteristics of Sasang typology. The correlation between YSR and SPQ subscales was investigated, and the differences of YSR among the high (30%), middle (40%), and low (30%) SPQ total score groups were examined with Analysis of variance. The profile analysis was also performed to compare YSR subscale profiles of three SPQ total score groups. Results: The SPQ total score significantly (p < 0.001) correlated positively with YSR externalizing problems (r = 0.293 and r = 0.248) and negatively with YSR internalizing problems (r = –0.211 and r = –0.150) in males and females, respectively. The YSR externalizing problem score is significantly higher in the high SPQ total score group (13.14 ± 9.33 and 10.03 ± 5.34 for males and females, respectively) than in the low SPQ total score group (8.18 ± 5.53 and 8.58 ± 5.73, respectively), and the YSR internalizing problem score is significantly higher in the low SPQ total score group (11.28 ± 8.92 and 12.97 ± 8.69 for males and females, respectively) than in the high SPQ total score group (9.35 ± 9.00 and 11.28 ± 7.58, respectively). The YSR profiles for three SPQ total score groups were significantly different for males (profile analysis, df = 12.324, F = 18.164, p < 0.001) and females (df = 12.677, F = 11.601, p < 0.001). Conclusion: These results could be recognized as the SPQ, and Sasang typology would be useful for predicting the pathological patterns even of psychological problems in high school students. This study would be useful for the screening of psychopathological problems and character development in adolescents.